Muslim divorces in Singapore : amongst the inter-ethnic groups - K.H Majeed Maiden (International Institute of Islamic Thought and Civilization (ISTAC) , International Islamic University Malaysia, 2022)
While inter-ethnic marriages are becoming increasingly common in society, inter-ethnic couples in Singapore have a higher divorce rate than mono-ethnic ones. Inter-ethnic marriages have proliferated in Singapore in recent years, and it is becoming increasingly required to give an analysis of the potentially critical aspects that might play a significant part in the dynamics of couples from an inter-cultural perspective. Given these facts, it is critical to identify the variables that contribute to the failure of inter-ethnic marriages amongst Muslim couples, but such study has been limited thus far. The study's goal is to discover and analyse the true causes of divorce among inter-ethnic Muslim couples in Singapore. The purpose of this research is to look at the reasons that contribute to the breakdown of inter-ethnic marriages. The research also aims to analyse the legislation and processes in Shariʿa courts and to offer measures to reduce inter-ethnic divorces among Singapore's Muslims. The study employs a qualitative approach. Interviews is performing with married couples who are suffering marital problems. The interview will also include Shariʿa court administrators in order to get their experience on the subject and to analyse divorce rules and procedures. According to the corpus of research, inter-ethnic marriages and partnerships are more likely to face barriers influencing marital happiness than mono-ethnic marriages. Several factors have been identify as contributing to inter-ethnic divorces, including English as Singapore's common language, an increase in people receiving post-secondary or higher education, a large permanent resident and non-resident population, and multiracial workplaces, universities, and neighbourhoods. According to the study, adultery, cultures, customs, desertion, and financial concerns all play a role in inter-ethnic divorces. The study's implications imply that married couples should take greater steps to compromise and develop their relationships with inter-ethnic couples. This might involve presenting programs developed expressly for preparing persons who choose inter-ethnic marriage. Due to the scarcity of past research, a greater knowledge of the variables impact inter-ethnic couples in Singapore appears to be a critical introduction to the local environment. In conclusion, this study emphasized the need of community education in understanding inter-ethnic marriages in Singapore's unique culture.